National Hospital Discharge Survey, 1976 ([Verlag nicht ermittelbar], 1993)
This survey, which is part of a continuing sample of hospital discharge records, supplies medical and demographic information used to calculate statistics on hospital utilization. This data collection consists of information abstracted from the face sheets of the medical records for sampled inpatients discharged from a national sample of nonfederal short-stay hospitals. Variables include information on the patient's demographic characteristics (sex, age, date of birth, race, marital status), dates of admission and discharge, status at discharge, diagnoses, procedures performed, and hospital characteristics such as number of beds, ownership, and region of the country.